2014
DOI: 10.1038/bmt.2014.259
|View full text |Cite
|
Sign up to set email alerts
|

Alternative donors extend transplantation for patients with lymphoma who lack an HLA matched donor

Abstract: Alternative donor transplantation is increasingly used for high risk lymphoma patients. We analyzed 1593 transplant recipients (2000 to 2010) and compared transplant outcomes in recipients of 8/8 allele human leukocyte antigen (HLA)-A, -B, -C, and DRB1 matched unrelated donors (MUD; n=1176), 7/8 allele HLA-matched unrelated donors (MMUD; n=275) and umbilical cord blood donors (1 or 2 units UCB; n=142). Adjusted 3-year non-relapse mortality of MMUD (44%) was higher as compared to MUD (35%; p=0.004), but similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…43 A study of 1593 lymphoma patients found similar overall among UCBT, 8/8 allele-matched unrelated bone marrow transplant and 7/8 allele-matched unrelated bone marrow transplant. 44 Chen et al 45 described similar disease-free survival among patients treated with RIC receiving either double UCBT or matched unrelated donor PBSC transplants at a single center. Results with haploidentical transplant continue to improve with the use of post transplant cyclophosphamide, pioneered at Johns Hopkins.…”
Section: Comparison Of Ucbt With Other Alternative Graft Sourcesmentioning
confidence: 96%
“…43 A study of 1593 lymphoma patients found similar overall among UCBT, 8/8 allele-matched unrelated bone marrow transplant and 7/8 allele-matched unrelated bone marrow transplant. 44 Chen et al 45 described similar disease-free survival among patients treated with RIC receiving either double UCBT or matched unrelated donor PBSC transplants at a single center. Results with haploidentical transplant continue to improve with the use of post transplant cyclophosphamide, pioneered at Johns Hopkins.…”
Section: Comparison Of Ucbt With Other Alternative Graft Sourcesmentioning
confidence: 96%
“…In recent years, alternative donor transplantation (umbilical cord blood or haploidentical marrow) has become more widespread, with recent publications showing outcomes that compare favorably to those using matched unrelated donors. [78,79] The haploidentical approach, with post-transplant cyclophosphamide, has successfully been applied to lymphoma patients up to age 75, with 1 year NRM of 10–15% across all age groups from 50–75, and a 3 year survival of approximately 50%. [80] With the growing use and success of alternative donor transplantation, it is expected that an even larger number of older patients will be allo-HCT candidates, since in many cases such patients do not have a matched sibling who is in good enough health to serve as a donor.…”
Section: Allogeneic Transplanation In Older Lymphoma Patientsmentioning
confidence: 99%
“…Allogeneic hematopoietic cell transplantation (HCT) can provide long-term survival for patients with various subtypes of lymphoma; however, relapse remains the predominant cause of treatment failure [1-4]. The use of 18 F-fluorodeoxy glucose (FDG)-positron emission tomography (PET) after front-line or salvage chemotherapy is a valuable prognostic tool to assess the depth of remission before autologous HCT [5-9].…”
Section: Introductionmentioning
confidence: 99%